2023
DOI: 10.1002/clt2.12274
|View full text |Cite
|
Sign up to set email alerts
|

The holo beta‐lactoglobulin lozenge reduces symptoms in cat allergy—Evaluation in an allergen exposure chamber and by titrated nasal allergen challenge

Abstract: Background The allergists´ tool box in cat allergy management is limited. Clinical studies have shown that holo beta‐lactoglobulin (holoBLG) can restore micronutritional deficits in atopic immune cells and alleviate allergic symptoms in a completely allergen‐nonspecific manner. With this study, we aimed to provide proof of principle in cat allergy. Methods A novel challenge protocol for cat allergy in a standardized ECARF allergen exposure chamber (AEC) was developed. In an open pilot study (NCT05455749), pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Clinical studies have shown that holo beta-lactoglobulin (holoBLG) can restore micronutritional deficits in atopic immune cells and alleviate allergic symptoms in a completely allergen-nonspecific manner ( 117 ). A recent study demonstrates protection against cat challenge in cat allergic human subjects ( 118 ). The effects of providing such micronutrition on a large scale to pre-atopic children is unknown, as yet.…”
Section: Prevention Of Childhood Asthmamentioning
confidence: 99%
“…Clinical studies have shown that holo beta-lactoglobulin (holoBLG) can restore micronutritional deficits in atopic immune cells and alleviate allergic symptoms in a completely allergen-nonspecific manner ( 117 ). A recent study demonstrates protection against cat challenge in cat allergic human subjects ( 118 ). The effects of providing such micronutrition on a large scale to pre-atopic children is unknown, as yet.…”
Section: Prevention Of Childhood Asthmamentioning
confidence: 99%